Analisis perlakuan akuntansi aset tetap berdasarkan PSAK No. 16 pada Puskesmas Bulangan Haji Pamekasan - Aminatus Zakhra, Romsi Agus Sugiono (University of Merdeka Malang, 2024)
The aim of this research is to find out how Fixed Asset Accounting is treated at the Bulangan Haji Pamekasan Community Health Center based on PSAK 16. This research uses a qualitative method with a descriptive approach. This research was carried out in four stages, namely, (1) Data collection, carried out by interviews and documentation, (2) Data reduction (3) Data presentation (4) Drawing conclusions. The results of this research indicate that the Bulangan Haji Community Health Center has recognized, measured, depreciated and presented fixed assets. The measurement and presentation of fixed assets carried out by the Bulangan Haji Community Health Center is still not in accordance with PSAK 16 because the Community Health Center does not add the costs incurred to acquire the fixed assets to the acquisition price of the fixed assets.